Government regulations, internal governance and the efficiency of accounting firms - Weiping Liu; Shixin Yang (Journal of Frontier in Economic and Management Research, 2025)
Currently, governments across the world are tightening the regulations on accounting industry. In such a context, the effects of government regulations and internal governance on the efficiency of accounting firms are studied using DEA-Tobit two-stage analysis framework and difference-in-difference (DID) method using internal financial data of accounting firms (2006 2016) in Guangdong province, China. The research results demonstrate that Chinese accounting firms show low comprehensive efficiency and resource allocation efficiency. Government regulations are significantly negatively correlated with the efficiency of accounting firms; while proper internal governance contributes to the improvement of the efficiency and has positive regulating effects on the efficiency loss caused by government regulations. furthermore, the accounting firms that have larger size and higher business concentration have the lower efficiency. higher specialization and industrial agglomeration degrees contribute more to the improvement of the efficiency. The results obtained suggest that if the rigorous government regulations can facilitate internal governance and construction of accounting firms; playing self-governance role as partners. Furthermore, the efficiency loss caused by the strict external regulations can be reduced to some extent.